2011
DOI: 10.1002/ps.2320
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, transport and degradation of fipronil termiticide in three Hawaii soils

Abstract: BACKGROUND: The behavior of the termiticide fipronil in soils was studied to assess its potential to contaminate ground and surface water. This study characterizes (1) adsorption of fipronil in three different soils, (2) transport of fipronil through leaching and runoff under simulated rainfall in these soils and (3) degradation of fipronil to fipronil sulfide and fipronil sulfone in these soils. RESULTS: The adsorption experiments showed a Freundlich isotherm for fipronil with Koc equal to 1184 L kg−1. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…In terms of soil characteristics, organic carbon (OC) content, clay content, clay mineralogy, and pH are known to affect the immobilization and degradation of pesticides (Barriuso et al, 1992;Hiller et al, 2008;Koskinen and Harper, 1990). The oxide character and content can also be influential, particularly in tropical soils such as those found in Hawaii (Assis et al, 2011;Shuai et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…In terms of soil characteristics, organic carbon (OC) content, clay content, clay mineralogy, and pH are known to affect the immobilization and degradation of pesticides (Barriuso et al, 1992;Hiller et al, 2008;Koskinen and Harper, 1990). The oxide character and content can also be influential, particularly in tropical soils such as those found in Hawaii (Assis et al, 2011;Shuai et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Fipronil was easier degraded than its metabolites in soils (Shuai et al, 2012;Spomer and Kamble, 2010). Our results found that Fipronil as an effective pesticides wound not cause earthworms death resulting in the reduce densities of earthworms in deep soil.…”
Section: Discussionmentioning
confidence: 63%
“…The measurements of pesticide residue in soil might not adequately predict long-term insecticidal efficacy, because they do not consider all the complex biotic and abiotic interactions that can have deleterious effects on the termiticides. Abiotic and biotic reactions (hydrolysis, photolysis, and oxidation) of insecticides designated for termite control have been documented (Austin 1999, Baskaran et al 1999, Kamble and Saran 2005, Shuai et al 2012. Other factors affecting efficacy of a termiticide are susceptibility and behavioral reaction of the termites to the chemical.…”
Section: Introductionmentioning
confidence: 98%